Influence of sewage treatment and urbanization on selection of multiple resistance in fecal coliform populations. - Bell, J B (1983)
The fecal coliform populations found in the raw sewages and final sewage effluents of mechanical treatment plants, a long-term retention lagoon, shorter-term retention lagoons, a remote northern Canada river, and a heavily urbanized prairie river were examined for antibiotic resistance and the possession of R factors. It was determined that there was a decrease in the percentage of multiresistant fecal coliform populations in the mechanical sewage treatment plants and shorter-term retention lagoons; however, there was an increase in populations from the long-term retention lagoon. The percentage of the populations possessing transmissible R factors was constant in the mechanical treatment and shorter-term retention facilities; however, the ability to transmit was lost in 50% of the infective population of the long-term retention facility. A striking contrast was found between the populations of the remote northern Slave River and those of the urbanized Red River. Of the fecal coliforms in the Slave River, 7.1% were multiresistant, and only 0.79% possessed transmissible R factors. The Red River fecal coliform populations were 52.9% multiresistant, and 18.77% of the total population possessed transmissible R factors. The influence of urbanization and the type of sewage treatment have been shown to affect the selection and survival of multiresistant fecal coliforms and R+ fecal coliforms. Determination of other factors influencing the development and the survival of these populations is needed for rational wastewater management and water quality consideration.